Influence of Social Media on Physicians’ Behaviors (International Journal of Scientific Research and Management (IJSRM), 2024)
The influence of social media on health-related behaviors is a major research topic. Social media platforms play a crucial role in disseminating health information, thus influencing individuals’ perceptions, attitudes, and behaviors towards health and healthcare. These platforms allow quick access to a large amount of information but can also convey inaccurate or misleading information. Social media also enables individuals to share their personal health experiences, which can influence the behavior of other users. Health awareness and promotion campaigns conducted on social media can have a significant impact by reaching a wide audience. Additionally, social media platforms have become popular spaces for healthcare professionals and healthcare organizations to interact with patients, answer their questions, and provide medical advice. However, excessive use of social media can also have negative effects on mental health, including contributing to anxiety, depression, and social isolation. It is therefore crucial to understand how social media shapes health-related behaviors in order to promote healthy behaviors and counter misinformation.